Meta-Emotion Philosophy Among Asian Indian Immigrant Mothers in the United States. (July 2014) - Fishman, Jonathan L.; Raval, Vaishali V.; Daga, Suchi S.; Raj, Stacey P.
We explored the meta-emotion philosophies of Indian immigrant mothers living in the Midwest region of the United States to expand the scarce literature on emotion socialization in diverse families. A total of 15 mothers of teen and preteen children participated in a meta-emotion interview, in which they were asked about their own and their children's experiences of anger, sadness, and fear. We analyzed interview responses through an open-ended phenomenological approach and found the following major themes: familial context of emotions, subtle communication of emotions, and an overarching philosophy centering on inevitability of negative emotions and the importance of moving on. Mothers differed in how well they believed that they could move on. Overall, the present findings demonstrate the role culture plays in emotional experiences of immigrant mothers and serve as a reminder that theories based on European American families might have limited applicability to other cultural and ethnic groups.